Critical care nursing review - Gossman, William G.; Plantz, Scott H. (New York : McGraw Hill Professional, 2007)
Useful for certification and re-certification, this review for the CCRN exam is an ideal compliment to larger texts for streamlined review in the days and weeks before your exam. This work enables you to maximise your exam preparation time.
AIRWAY, RESUSCITATION AND VENTILATOR PEARLS -- SHOCK PEARLS -- CARDIOVASCULAR PEARLS -- TRAUMA PEARLS -- HEAD AND NECK PEARLS -- PULMONARY PEARLS -- GASTROINTESTINAL PEARLS -- GENITOURINARY/RENAL PEARLS -- NEUROLOGY PEARLS -- INFECTIOUS DISEASE PEARLS -- HEMATOLOGY AND ONCOLOGY PEARLS ELECTROLTYE, ACID-BASE AND ENDOCRINE PEARLS -- TOXICOLOGY PEARLS -- NUTRITION MANAGEMENT PEARLS -- IMMUNOLOGY AND TRANSPLANTATION PEARLS -- ETHICS AND PAIN MANAGEMENT -- BIBLIOGRAPHY.
Keywords: INTENSIVE CARE NURSING -- EXAMINATIONS, QUESTIONS, ETC; NURSING DIAGNOSIS; INTENSIVE CARE NURSING